CHROMIUM CONTENT OF MILK-FISH (Chanos chanos, Forskal) IN BRACKISH WATER POND AROUND BABON RIVER OF SEMARANG COASTAL AREAS, CENTRAL JAVA, INDONESIA - Nanik Heru Suprapti (JOURNAL OF COASTAL DEVELOPMENT, 1999)
The aims of study were to determined Cr content in water and in Milk-fish around Babon River Estuary Semarang. Water drinking Criteria issued by Indonesian Ministry of Environmental and Concentration Factors Index were used for analysise the Chromium content. The results indicated that Chromium content in water and Milk-fish were over of the recommended maximum level. The value of concentration factor index of the Cr content had been found low up to accumulation